Antioxidant Effect of Bilimbi Fruit (Averrhoa Bilimbi Linn) Extract on SGPT Level in Mice Induced by Reheated Palm Oil - Mulyono, Rosi Dwi; Putranto, R Prihandjojo Andri; ., Sarsono (Nexus Kedokteran Translasional, 2016)
Introduction: Reheated palm oil was known to contain free radicals that cause damage and death of liver cell, antioxidant is needed to prevent. One source of antioxidant is Bilimbi fruit. This research aims to determine the effect of Bilimbi fruit extract and variant in dosage of Bilimbi fruit extract on levels of Serum Glutamic Piruvic Transaminase in mice induced by reheated palm oil. Methods: This research was a laboratory experimental with a post-test only control grup design. The subject of research was Swiss Webster mice, male, age 2-3 mounths, weight + 20 grams. The subject ware chosen by incidental sampling for 30 individuals, devided randomly into 5 groups, each groups consist of 6 mice. The control group (K) was given aquadest (0,3 ml/20 g BW and 0,2 ml/20 g BW). Mice in treated group 1 (P1) was given aquadest (0,3 ml/20 g BW) and reheated palm oil (0,2 ml/20 g BW). Mice in treated group 2 (P2), treated group 3 (P3) and treated group 4 (P4) was given Bilimbi fruit extract with dosage 5,6 mg/20 g BW; 11,2 mg/20 g BW; and 22,4 mg/20 g BW and reheated palm oil (0,2 ml/20 g BB). Bilimbi fruit extract was given 1 hour before reheated palm oil for 14 days. At the day-15, mice ware sacrificed and the animal blood was collected from pleksus retroorbitalis. The result was analyzed statistically by one way ANOVA and followed by LSD test (Î± =Â  0,05). Results: Mean of SGPT level in each group was K = 37,5 + 8,256 U/L; P1 = 50,92 + 8,267 U/L; P2 = 37,08 + 5,043 U/L; P3 = 43,34 + 7,834 U/L; P4 = 51,12 + 13,526 U/L. There wes significant difference between K â P1, K â P4, P1 â P2, and P2 â P4, there was not significant difference between K â P2, K â P3, P1 â P3, P1 â P4, P2 â P3, and P3 â P4. Conclusions: The extract of Bilimbi fruit decrease SGPT level in mice induced by reheated palm oil. An increase in dose of Bilimbi fruit extract cannot increase the influence to decrease SGPT level in mice induced by reheated palm oil. Keywords: Bilimbi fruit extract, SGPT, reheated palm oil, SGPT.Â